Pre-tactical trajectory compatibility determination to reduce air traffic controllers' tactical workload - Portillo, Yolanda (Cranfield University, 2012)
The current Air Traffic Management (ATM) system, based on principles established more than 50 years ago, is starting to show clear signs of saturation. This fact. joined to increasingly environmental awareness, leads to a paradigm shift from the current sector-based ATM system, to a future trajectory-based ATM system. Within this research, factors and processes affecting trajectory-based operations are analysed, and the main factors hindering an accurate trajectory definition identified, in order to establish the criteria under which two aircraft trajectories could be declared as compatible in a pre-tactical management stage. Trajectory compatibility determination will endeavour to reduce the real-time Air Traffic Controller‟s (ATCO‟s) workload in the tactical stage, currently identified as one of the main bottlenecks in the existing ATM system. The obtained results are based on a trade-off between the system capacity, understood as the number of ATCO tactical interventions, versus the system predictability, as the number of misdetections or probability of conflict to be assumed in a pre-tactical timeframe. A criterion to identify when two trajectories are compatible is presented, firstly considering the movement as horizontal only, then including the vertical components when one or both aircraft are climbing or descending. The research initial results were presented in a Paper in the first SESAR Innovation Days which took place at Toulouse from the 29th of November 2011 to the 1st of December 2011 (Paper included as Annex V).